PENGARUH METODE LATIHAN KONSEP “BEEF” TERHADAP PENINGKATAN SHOOTING PADA PESERTA EKTRAKURIKULER BOLA BASKET SMPN 1 SUKATANI - Riswan -; Nana Suryana Nasution; Fahrudin (Jurnal Speed (Sport, Physical Education, Empowerment), 2021)
ABSTRACT: The study aims to understand the effects of meeting contact with meetode the concept "beef," "beef" - the concept of shooting involving balance, eyes, elbow (elbow), and follow through (advanced movement after release of the ball). For the increased basketball shooting skills for international high school seniors. The method used in this research is pre-experiment, it goes into the form of one group prepackaged posttest design. The population in this study are participants who follow extracurricular basketball. Sampling USES an impressive. sample, by criteria: extracurricular basketball participants are still active, sample number 25 children. The instrument used is the "beef" shooting test validated by the basketball coach, the data analysis using the t-test and analysis shows that: there's a difference between the "beef" shooting. From data of the t test it can see that the t count is greater than t table (48.12 > 0.05) and the significant p value of (27.88 < 0.05) this result shows that there is a significant difference between pretest and postest. Pretest data has an average of 27.88 and the postest average of 48.88. The conclusion of the shooting practice with the concept of beef was able to improve the basketball shooting skills for beginners. The volume of the shooting range was seen from the average difference of 20.24 Keywords : Extracurricular, shooting skills with concept methods “BEEF”